D-cleft: An innovative method for feeding neonates born with cleft palate - Anubhav Jannu; Abhishek Nagaraj; Ruchi Gupta (Wolters Kluwer Medknow Publications, 2017)
Introduction: Babies born with cleft palate suffer from feeding problems which interfere with their nutrition and development; thereby, hampering the criteria for subsequent corrective surgery. The palatal cleft interferes with nursing and causes insufficient suckling or nasal regurgitation of food. Because of altered anatomy and presence of oro-nasal fistula, baby tends to present suction difficulties due to lack of negative intraoral pressure. Upper respiratory tract infection and chronic catarrh are not frequent. Materials and Methods: Here is a patented device for attaching on commercially-available feeding bottles to facilitate effective nutrition method. The device's journey from concept to clinical use has been presented with a case series. Results: The device was tried and tested successfully in many babies born with Cleft palate. It has been successfully used to feeding neonates by their mothers/care-takers with almost no training required. Conclusion: The device is extremely easy to use, easy to maintain and economical. In cases where modifying the feeding position alone cannot make much difference, these attachments can be advocated.